Geodetic Reference Frames IAG Symposium Munich, Germany, 9-14 October 2006 - Drewes, Hermann (International Association of Geodesy Symposia, 2009)
Geodetic reference frames are the basis for The programme of the Symposium was divided three-dimensional, time dependent positioning according to the Sub-commissions, Projects in all global, regional and national networks, in and Study Groups of Commission 1 into eight cadastre, engineering, precise navigation, geo- general themes: information systems, geodynamics, sea level studies, and other geosciences. They are 1. Combination of space techniques necessary to consistently estimate unknown 2. Global reference frames and Earth rotation parameters using geodetic observations, e. g. , 3. Regional reference frames station coordinates, Earth orientation and 4. Interaction of terrestrial and celestial frames rotation parameters. Commission 1 "Reference 5. Vertical reference frames Frames" of the International Association of 6. Ionosphere modelling and analysis Geodesy (IAG) was established within the new 7. Satellite altimetry structure of IAG in 2003 with the mission to 8. Use of GNSS for reference frames study the fundamental scientific problems for the establishment of reference frames. One day of the Symposium was dedicated to a The principal objective of the scientific work joint meeting with the International Congress of the Commission is basic research on: of Federación Internationale des Géomètres - Definition, establishment, maintenance, and (FIG) and the INTERGEO congress of the improvement of geodetic reference frames. German Association of Surveying, Geo- - Advanced development of terrestrial and information and Land Management. The space observation techniques for this contributions presented at this meeting are purpose. integrated into these proceedings.